Exergoeconomic analysis of a rotary kiln used for plaster production as building materials - Gurturk, Mert; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2016)
This study has been proposed to determine the production of the cost of the plaster production and present some solutions, techniques and processes especially for rotary kiln to reduce the cost of plaster production which is used as building material. The rotary kilns consume the highest energy in any processes. Thus, the exergoeconomic analysis of the rotary kiln used for plaster production was carried out by using actual operational data to see its effectiveness. The exergy cost is 593.6 US$/h and the cost per unit exergy is 1502.4 US$/GJ of the Calcium sulfate hemihydrate (CSH) or plaster produced by the system. The capital cost flow is very high due to the hourly levelized operating and maintenance cost. Especially, the transport cost of the raw materials or the CSD is very high due to be far away of distance between the gypsum quarry and the plaster plant. The exergoeconomic factor of the rotary kiln is calculated as 70%. The exergy loss and destruction should be considered for reducing production cost. The results of the exergoeconomic analysis are evaluated different perspectives for reducing the production cost. The specific manufacturing cost of the CSH is found as 0.03 US$/kg. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Rotary kiln; Exergoeconomics; Plaster; Gypsum